2010
DOI: 10.1186/1756-3305-3-58
|View full text |Cite
|
Sign up to set email alerts
|

Urinary schistosomiasis among preschool children in a rural community near Abeokuta, Nigeria

Abstract: BackgroundThe control of schistosomiasis in Nigeria is mainly by mass treatment with praziquantel through the school system, with an absence of any provision for pre-school children. We therefore determined the prevalence and intensity of urinary schistosomiasis in pre-school children between the ages of 1-6 years in Ilewo-Orile a rural and endemic community, near Abeokuta, Nigeria as part of providing information on the neglected tropical diseases among this age group. Two urine samples were collected from ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
109
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(141 citation statements)
references
References 14 publications
(17 reference statements)
16
109
15
1
Order By: Relevance
“…Urinalysis reagent strips (Cortez Diagnostics Inc., Woodland Hills, CA, USA) were used to detect the presence of haemoglobin in the urine, following methods described by Ekpo et al 21 The colours found on the strips were directly compared to the colours indicated on the reagent strip bottle in order to determine the exact category of the colour. The colour values were labelled as negative (-), slightly positive (+), positive (++), and strongly positive (+++), each corresponding to the amount of blood found in the urine sample being tested.…”
Section: Examination Of Urine For Microhaematuriamentioning
confidence: 99%
See 2 more Smart Citations
“…Urinalysis reagent strips (Cortez Diagnostics Inc., Woodland Hills, CA, USA) were used to detect the presence of haemoglobin in the urine, following methods described by Ekpo et al 21 The colours found on the strips were directly compared to the colours indicated on the reagent strip bottle in order to determine the exact category of the colour. The colour values were labelled as negative (-), slightly positive (+), positive (++), and strongly positive (+++), each corresponding to the amount of blood found in the urine sample being tested.…”
Section: Examination Of Urine For Microhaematuriamentioning
confidence: 99%
“…based on morphological identification keys. 19,20,21 Those that were identified as Bulinus globosus were counted and the rest were thrown back into the water.…”
Section: Snail Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Village primary school children are particularly vulnerable to schistosomiasis because of their routine habit and lifestyle. Water contact recreational activities among primary school children between the ages of 5-15 years old includes bathing, swimming, drinking, washing clothes or kitchen utencils and fetching of water, are generally the norm which serves as potential source of transmission 16 . Systematic schistosomicidal treatment had never been applied in the village 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Water contact recreational activities among primary school children between the ages of 5-15 years old includes bathing, swimming, drinking, washing clothes or kitchen utencils and fetching of water, are generally the norm which serves as potential source of transmission 16 . Systematic schistosomicidal treatment had never been applied in the village 16 . Infection with urinary schistosomiasis occurs very early in life through exposure to contaminated water bodies.…”
Section: Introductionmentioning
confidence: 99%